Correction: Guidelines for the prevention, detection and management of the renal complications of COVID-19 in Africa - Elsayed, Hesham M; Wadee, Shoyab; Zaki, Mohamed S; Were, Anthony JO; Ashuntantang, Gloria E; Bamgboye, Ebun L; Davids, Mogamat Razeen; Hafez, Mohamed H; Mahamat, Maimouna; Naicker, Saraladevi; Niang, Adbou; Seck, Sidy M; et al. (African Journal of Nephrology, 2020)
The authors of the article ‘Guidelines for the prevention, detection and management of the renal complications of COVID-19 in Africa’ [1] wish to acknowledge the contribution of Professor Hussein El Fishawy. Our guidelines drew on various sources, including the Egyptian Ministry of Health guidelines, portions of which were adapted and reproduced with permission from the Egyptian Ministry of Health. Two of the authors of those guidelines, Professors Elsayed and Zaki, are also coauthors of our paper. Professor El Fishawy was the third author of the Egyptian guidelines and we would like to acknowledge his contribution to our review through this source, especially with respect to the treatment algorithms for patients with kidney transplants and those with acute kidney injury. Reference 1. Elsayed HM, Wadee S, Zaki MS, Were AJO, Ashuntantang GE, Bamgboye EL, et al. Guidelines for the prevention, detection and management of the renal complications of COVID-19 in Africa. Afr J Nephrol. 2020; 23(1):109-126.